Microplastic pollution in surface seawater of Sanggou Bay, China: Occurrence, source and inventory. (January 2021) - Xia, Bin; Sui, Qi; Sun, Xuemei; Zhu, Lin; Wang, Rongyuan; Cai, Minggang; Chen, Bijuan; Qu, Keming
Abstract: Microplastic pollution in marine environments has become a major global environmental issue. However, the source of microplastics in marine environments is poorly understood. Here, we investigated the distribution and the source of microplastics in surface seawater from Sanggou Bay, China. The results showed that the average abundance of microplastics was 20.06 ± 4.73 items/L, which represented a medium and high level relative to other sea areas. Microplastics of <0.5 mm dominated. Most particles were granular and transparent, and polyethylene was the dominant polymer. We estimated that 62.76% of the microplastics originated from mariculture facilities, an indication that mariculture contributes significantly to microplastics pollution, and calculated that 96.15 kg was present in surface seawater of Sanggou Bay. Our findings indicated that more attention should be paid to mariculture-derived microplastics pollution in the future. Graphical abstract: Unlabelled Image Highlights: Microplastic pollution was at a medium and high level relative to other areas Estimated 62.76% of microplastics derived from mariculture plastic facilities Estimated microplastics inventory in surface seawater of Sanggou Bay was 96.15 kg Mariculture-derived microplastic should be paid more attention to